ETHNIC RELATIONS IN THE CITY OF PONTIANAK (A STUDY OF INTER-ETHNIC RELATIONS AT GANG DAMAI, KOTA BARU, PONTIANAK) - Ibrahim MS (Graduate Program of Pontianak Institute of Islamic Studies, 2012)
Peace and harmony in life is one of the goals of the communities at Gang Damai in their social relations. This condition becomes very special when, in other places at the same time, conflicts and hostilities often occurred in the history of inter-ethnic relations in this region. This is the underlying reason of the naming of the place of this research i.e. “Gang Damai” (peaceful alley). This study found four key factors underlying the harmony and good relations between the ethnic groups; first, a positive outlook on the ethnic communities; second, distinctive efforts undertaken by the community members in order to continue to maintain good social relations, security, peace and harmony; third, awareness practiced by all communities in an effort to build and maintain social relations in the spirit of solidarity; fourth, different ethnic communities manage to minimize all forms of issues that could potentially become a trigger for conflicts by building intensive communication and social relations among themselves. In addition, unique social relation patterns built and inter-ethnic marriages have also become a model in building peaceful ethnic relations at Gang Damai until today. Keywords: Peace, Harmony, Social Relations, Ethnicity